Pengembangan Game Edukasi Galoris-x Pada Materi Perkalian Kelas IV SDN Morombuh 1 Bangkalan - Nor Aida Amalia Putri; Nova Estu Harsiwi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to develop a valid, practical, and effective galoris-x educational game learning media for the multiplication of whole numbers up to 100 for fourth-grade students of SDN Morombuh 1. This study uses the ADDIE (Analysis, Design, Development, Implementation, & Evaluation) research model. This study is motivated by the low learning outcomes of students on the multiplication material of 67 who have not reached the KKTP set at 70, and also learning that is still monotonous and uses lecture methods and does not use learning media. The validity of the product is obtained from the media expert validator obtaining a percentage of 94% (very valid), learning material experts 82.2% (very valid), and learning design experts and 96% (very valid). The practicality of the developed galoris-x educational game media is stated to be practical as assessed from the results of the teacher response questionnaire showing a percentage of 98% with a very practical category, and the student response questionnaire showing a percentage of 97.7% with a very practical category. The effectiveness of the Galoris-X educational game media has been declared effective based on the observation results of teacher and student activities during 2 meetings, meeting 1 teacher activity obtained 90% (very effective), student activity 89.5% (very effective). Meeting 2 teacher activity obtained 95% (very effective), student activity 93% (very effective). Learning outcomes based on the paired sample t test obtained a result of 0.000. <0.05 and a sig value of 15.199> 2.145 so that Ho is rejected Ha is accepted there is a difference between the scores of fourth grade students of SDN Morombuh 1 on multiplication material before and after learning using the Galoris-X educational game.